From Nature to iNature. Articulating a Sami Christian Identity Online - Torjer Olsen (Nordlit: Tidsskrift i litteratur og kultur, 2012)
The article discusses the activities of both indigenous people and religion online, and introduces the pair of concepts indigeneity-online/online-indigeneity as a means of analysing this activity. This concept is new, and leans heavily on the pair of concepts religion-online/online-religion that is used in religious studies. The second part of the article consists of an analysis of the website www.osko.no, a site for the Christian education of Sami children and youth. I treat this as an expression of, or a medium for, the contemporary formation of Sami identity, and argue that it can be seen as an indigenous website. The Church of Norway, as an institution with a strong history of colonization  and  Norwegianization, has  developed  into an  institution  that  seeks  to integrate, implement and strengthen the Sami voices and traditions to such extent thatSami  Christians  use  it  as platform  for  the  communication  of  a Sami  kind of Christianity. www.osko.no is an example of a certain articulation of Sami identity. What seems  to  be  the  preferred  or idealized  Saminess  is  related  to nature and  a particular past, and is distant to modernity, urban culture and Norwegian culture.